PERANCANGAN SISTEM INFORMASI PELANGGAN PASIEN PADA RUMAH SAKIT JIWA (RSJ) ACEH - Anggrainy, Hawilah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2021)
The research objectives are; To find out the Patient Information System at the Aceh Mental Hospital (RSJ) and Design a Patient Information System at the Aceh Mental Hospital (RSJ) using Visual BASIC.NET. Broadly speaking, this research is divided into three stages, namely pre-development data collection, development and implementation, and post-development data collection. While in software development using the DSRM (Design Science Research Method) method. With the existence of this patient information system program, the information system at the Aceh Mental Hospital (RSJ) becomes precise, and accurate, especially on the patient side. And to obtain information about the patient becomes easier; This information system is able to overcome the problems that often occur in the Aceh Mental Hospital (RSJ), namely the difficulty in controlling and supervising patients and planning for procurement of goods. This goods procurement information system can avoid excess patients and overcome the scarcity of goods which is certainly highly expected by business actors and the creation of an information system program in order to obtain quality information.